Adrenal myelolipoma - an enigma - Mohammad Amjad, Nasser; J, Kassian; S, Baharudin; R, Kalavathy (OMICS Publishing Group, 2012)
Adrenal myelolipomas are rare neoplasms. They are benign in nature comprising mainly of adipose and myeloid tissues. Majority of these adrenal gland tumors are hormonally inactive. In view of their rarity, they are usually detected incidently or misdiagnosed. Misdiagnosis is quite common and can lead to difficulty in management. We wish to report a case of adrenal myelolipoma that was misdiagnosed which fortunately did not result in a major issue. With the availability of advanced imaging techniques and minimally invasive procedures these situations can easily be avoided. The main reason for highlighting this patient is to create awareness among both the surgeons and the radiologists.